FECUNDITY AND THE BODY LENGTH OF RAG WORM, PERINEREIS CULTRIFERA (GRUBE 1840) FROM WEARLILIR BEACH WATERS, SMALL KEI ISLANDS, SOUTHEAST MALUKU DISTRICT - Martha Rettob (JOURNAL OF COASTAL DEVELOPMENT, 2012)
The knowledge of fecundity is an important aspect in the reproductive biology. Understanding the fecundity may allow the estimation of the number of rag worm individual and the determination of the number of rag worm in the questioned length class. The number of egg released represents a linking chain for one generation to next generation. The objective of research is to understand the range of fecundity, the range of body length, and the relationship of fecundity and body length of rag worm from Wearlilir waters, Moluccas, Indonesia. Achieving this objective, the observation  to 238 individuals of female rag worm which are captured at Wearlilir beach waters, Small Kei Islands, Southeast Maluku District for a year from June 2010 to May 2011. The fecundity is calculated with the mixed methods including volumetric, gravimetric, and arithmetic. The relationship between fecundity and body length of rag worm is following the square function, F = 144.6533PT1.2911. It can be transformed into a form of natural logarithm to produce the regression equation: ln (WF) = 4.97434 + 1.29109 * ln (WP). Result of linear regression analysis of variance indicates that there is a positive relationship between the fecundity and body length. This relationship is not so close because only 26 % fecundities are influenced by the length, while 74 % are influenced by other factors such as environment and food.